The effect of lithium on the metabolism of GABA in the hyperammonemic rat brain - Baydas, G.; Turkoglu, A.; Karakilcik, Z.; Aksakal, M.; Ozguner, F.; Gursu, F. (My University, 1992)
[Abstract Not Available]
Keywords: 4 aminobutyric acid; ammonia; lithium carbonate; 4 aminobutyric acid brain level; animal experiment; article; hyperammonemia; intraperitoneal drug administration; male; nonhuman; rat